An extreme-phenotype genome‐wide association study identifies candidate cannabinoid pathway genes in Cannabis - Matthew T. Welling (Nature Portfolio, 2020)
Abstract Cannabis produces a class of isoprenylated resorcinyl polyketides known as cannabinoids, a subset of which are medically important and exclusive to this plant. The cannabinoid alkyl group is a critical structural feature that governs therapeutic activity. Genetic enhancement of the alkyl side-chain could lead to the development of novel chemical phenotypes (chemotypes) for pharmaceutical end-use. However, the genetic determinants underlying in planta variation of cannabinoid alkyl side-chain length remain uncharacterised. Using a diversity panel derived from the Ecofibre Cannabis germplasm collection, an extreme-phenotype genome-wide association study (XP-GWAS) was used to enrich for alkyl cannabinoid polymorphic regions. Resequencing of chemotypically extreme pools revealed a known cannabinoid synthesis pathway locus as well as a series of chemotype-associated genomic regions. One of these regions contained a candidate gene encoding a β-keto acyl carrier protein (ACP) reductase (BKR) putatively associated with polyketide fatty acid starter unit synthesis and alkyl side-chain length. Association analysis revealed twenty-two polymorphic variants spanning the length of this gene, including two nonsynonymous substitutions. The success of this first reported application of XP-GWAS for an obligate outcrossing and highly heterozygote plant genus suggests that this approach may have generic application for other plant species.